The Effect Of Focus Group Discussion On Female Adolescents’ Knowledge Of Menstual Cycle - Sulistiyowati Sulistiyowati (Universitas Islam Lamongan, 2022)
Menstrual cycle is a sign of the maturity process of the reproductive organs and is closely related to hormones. A normal menstrual cycle occurs every 21-35 days with a duration of 2-7 days. It was found that there were many female adolescents who did were not aware of their menstrual cycles. The current study aimed to identify female adolescents’ knowledge of menstrual cycle both before and after the treatment and to analyze the effect of focus group discussion on the knowledge improvement.This research used pre-experimental design with one group pretest-posttest approach. The population was all female students in class VIII A and VIII B at SMP Negeri 1 Pucuk on July 2022 as many as 32 students with a sample size of 28 students using simple random sampling with lottery techniques, treatment with the Focus Group Discussion method. After the data was collected, it was then tabulated and analyzed using the Wilcoxon Sign Rank Test.The results showed that 27 out of 28 (96%) respondents had good knowledge of menstrual cycle after focus group discussion was held while only 1 (4%) respondent had fair knowledge. Meanwhile, from the statistical test results, it was found that there was an effect of focus group discussion on female adolescents’ knowledge of menstrual cycle with a value of -4.919a with a significance level of p <0.05.From the results, it is expected that respondents can apply the knowledge they gained so that they can be better in thinking and acting.